Diamine and polymer using the same

A fully aliphatic diamine with a cage-like silsesquioxane structure addresses the high dielectric loss challenge in polyimides by forming polymers with low dielectric constant and loss tangent, suitable for transparent and high-frequency applications.

JP2025009145APending Publication Date: 2025-01-20JNC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023111944
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing polyimides used in electronic circuits face challenges in achieving low dielectric loss due to their polar groups, making it difficult to reduce dielectric loss tangent, especially at high frequencies, which leads to issues like heat generation, signal attenuation, and delay.

Method used

A fully aliphatic diamine with a cage-like silsesquioxane structure is introduced, which reacts with tetracarboxylic dianhydride to form polymers such as polyamic acid, polyimide, or polyamideimide, incorporating a cage-like silsesquioxane structure into the main chain, resulting in low dielectric constant and low dielectric loss tangent.

Benefits of technology

The resulting polymers exhibit low dielectric constant and dielectric loss tangent, enabling the production of low dielectric materials suitable for electronic devices and optical members that require transparency and high-frequency signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009145000001_ABST
    Figure 2025009145000001_ABST
Patent Text Reader

Abstract

To provide: a diamine having a fully aliphatic cage-like silsesquioxane structure and having no aromatic ring structure; a polymer of a polyamic acid, a polyimide, a polyamide or a polyamideimide derived from a fully aliphatic diamine having a cage-like silsesquioxane structure; and a low dielectric member or an optical member using a film, being a thin film or a self-supporting film, made of the polymer.SOLUTION: A fully aliphatic silsesquioxane diamine having a cage structure is obtained by changing a substituent at an apex of the cage structure from an aromatic group to an aliphatic group, preferably to an alicyclic group. Additionally, this aliphatic diamine and a tetracarboxylic dianhydride are made to react with each other so as to obtain polymers of a polyamic acid, a polyimide, a polyamide or a polyamideimide in which a fully aliphatic cage-like silsesquioxane structure, preferably a fully alicyclic cage-like silsesquioxane structure indispensable for a low dielectric member or a colorless transparent polyimide material is introduced into the main chain.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a diamine and a polymer using the same, more specifically to a diamine having a silsesquioxane skeleton and a polymer using the same. More specifically, the present invention relates to a fully aliphatic diamine having a cage-shaped silsesquioxane structure with a vertex aliphatic substituent, preferably a vertex alicyclic substituent, and a polyamic acid, polyimide, polyamide or polyamideimide polymer having a cage-shaped silsesquioxane structure in the main chain derived therefrom, as well as a protective film, an insulating film, a low dielectric member and an optical member using a thin film or a free-standing film made of these polymers, or an electronic device or an optical device using the thin film or the free-standing film. [Background technology]

[0002] In recent years, signal frequencies have been increasing in response to the demand for ultra-high speed and large capacity information transmission. Higher frequencies increase the transmission loss of substrate materials for electronic circuits and antennas, resulting in problems such as heat generation in printed wiring boards and signal attenuation and delay. Transmission loss includes conductor loss caused by the conductors that form the transmission circuit and dielectric loss caused by the consumption of the electric field energy of the signal by insulators. In the high frequency range, the contribution of dielectric loss is large, and low dielectric loss materials with low dielectric loss are required as insulators for printed wiring boards of high frequency circuits. Since dielectric loss is proportional to the square root of the dielectric constant or dielectric loss tangent of the substrate material or resin, it is considered that the most effective way to reduce dielectric loss is to reduce the dielectric loss tangent of the substrate material or resin, which is a dielectric.

[0003] Polyimides, which have high insulating properties and reliability, have been widely used in electronic devices and electronic components such as circuit boards. Since polyimides contain many polar groups, it is very difficult to achieve low dielectric loss. Generally, methods to lower the dielectric constant and dielectric loss tangent are introduced by fluorine or by making the polyimide porous.

[0004] In recent years, polyhedral oligomeric silsequioxanes (POSS) have attracted attention, and various methods have been proposed to introduce their structures into polyimides. In a report by Nishiura et al. (see, for example, Patent Documents 1 and 2), a partially cleaved structure of POSS was mixed with polyimide to improve the problem of lack of uniformity in the thickness of the polyimide film in a conventional POSS and polyimide dispersion system, thereby succeeding in reducing the dielectric tangent. In addition, a polymer such as polyimide obtained by dehydrating and ring-closing polyamic acid having a cage-shaped silsesquioxane structure introduced into the main chain as a low dielectric material composition has also been reported. The cage-shaped silsesquioxane diamines used in the synthesis of these polyamic acids and polyimides are characterized in that the apex substituent of the cage structure is an aromatic diamine having a benzene ring. Although the polyamic acid and polyimide obtained by using the aromatic diamine of this cage-shaped silsesquioxane can be used as a low dielectric loss material with low dielectric loss, further reduction in dielectric loss is required. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-107121 A [Patent Document 2] JP 2013-18806 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the problems associated with the prior art described above, an object of the present invention is to provide an optical component such as a low dielectric component or a transparent polyimide material, and to this end, to provide a fully aliphatic cage-type silsesquioxane diamine that provides a low dielectric component or optical component. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and have succeeded in obtaining a silsesquioxane fully aliphatic diamine having a cage structure by making both the substituent at the apex of the cage structure and the substituent directly bonded to the amino group aliphatic. In addition, by reacting this aliphatic diamine with a tetracarboxylic dianhydride, a polymer of polyamic acid, polyimide, polyamide, or polyamideimide having a fully aliphatic cage silsesquioxane structure, preferably a fully alicyclic cage silsesquioxane structure, which is essential for optical components such as low dielectric components and colorless and transparent polyimide materials, introduced into the main chain. Furthermore, it has been found that the cured film obtained from these polymers has a significant effect on improving dielectric loss, and the present invention has been completed.

[0008] The present invention includes the following configurations. [1] A diamine represented by formula (1). TIFF2025009145000002.tif4186In formula (1), X is independently an alkylene having 1 to 12 carbon atoms or a cycloalkylene having 4 to 8 carbon atoms; in this alkylene having 1 to 12 carbon atoms, at least one hydrogen may be replaced by fluorine, R is independently an alkyl having 1 to 45 carbon atoms or a cycloalkyl having 4 to 8 carbon atoms; in this alkyl having 1 to 45 carbon atoms, at least one hydrogen may be replaced by fluorine and at least one -CH2- may be replaced by -O-, and in the cycloalkylene having 4 to 8 carbon atoms, at least one hydrogen may be replaced by fluorine or an alkyl having 1 to 3 carbon atoms; and R' is independently methyl or cyclohexyl. However, when X is alkylene having 1 to 12 carbon atoms; and in this alkylene having 1 to 12 carbon atoms, at least one hydrogen may be replaced by fluorine, R is not alkyl having 1 to 45 carbon atoms; and in this alkyl having 1 to 45 carbon atoms, at least one hydrogen may be replaced by fluorine and at least one -CH2- may be replaced by -O-. [2] The diamine of [1], wherein X is propylene or cyclohexylene; and R is methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tertiary butyl, cyclopentyl, or cyclohexyl. [3] The diamine according to [1] or [2], wherein X is 1,4-cyclohexylene; and R is cyclohexyl. [4] A polyamic acid obtained by reacting a raw material containing the diamine according to any one of [1] to [3] and a tetracarboxylic dianhydride. [5] A polyimide obtained by cyclizing the polyamic acid according to [4] above. [6] A polyamide obtained by reacting a raw material containing the diamine according to any one of [1] to [3] and a dicarboxylic acid or a derivative thereof. [7] A polyamideimide obtained by reacting a raw material containing the diamine according to any one of [1] to [3] and a tricarboxylic acid or a derivative thereof. [8] A thin or free-standing film made of the polyamic acid according to [4], the polyimide according to [5], the polyamide according to [6], or the polyamideimide according to [7]. [9] An insulating film using the film described in [8].

[10] A protective film using the film described in [8].

[11] A low dielectric component using the film described in [8].

[12] An optical component using the film described in [8].

[13] An electrical solid-state device using the insulating film according to [9].

[14] An electrical solid-state device using the protective film according to

[10] .

[15]

[11] A low dielectric material according to the present invention; The ability to generate, convert, transmit, and process radio frequencies and an electronic device having at least one capability selected from the group consisting of: electronic equipment.

[16] An optical device using the optical member described in

[12] . Effect of the Invention

[0009] The diamine of the present invention is a fully aliphatic diamine that does not have an aromatic ring structure and has a cage-shaped silsesquioxane structure. By using the diamine of the present invention, a polyamic acid, polyimide, polyamide or polyamideimide polymer having a silsesquioxane structure introduced into the main chain (hereinafter, sometimes referred to as the polymer of the present invention) can be obtained. The cured film obtained by curing the polymer having a cage-shaped silsesquioxane structure and an aliphatic structure, preferably an alicyclic structure, in the main chain of the polyamic acid exhibits a low dielectric constant, a low dielectric loss tangent and transparency. Therefore, by using the cured film obtained from the polymer of the present invention, it is possible to prepare low dielectric members such as low dielectric substrates, interlayer insulating films for low dielectric substrates, or low dielectric coating materials, and electronic devices such as electronic circuits, sensors, antennas, and radars using these, or electronic devices using these low dielectric members and electronic devices, and optical members that require transparency. [Brief description of the drawings]

[0010] [Figure 1] 1 is an IR spectrum of di[9,19-methyl(4-aminocyclohexyl)]-1,3,5,7,11,13,15,17-octacyclohexylpentacyclo[11.7.1.13,11.15,17.17,15]decasiloxane (compound 2), which is a diamine of the present invention synthesized in [Synthesis Example 1]. Compound 2 corresponds to the compound in which X is 1,4-cyclohexylene, R is cyclohexyl, and R' is methyl in the above formula (1). [Diagram 2] 2 is an IR spectrum diagram of benzeneamine, 4,4'-(9,19-dimethyl-1,3,5,7,11,13,15,17-octaphenylpentacyclo[11.7.1.13,11.15,17.17,15]decasiloxane-9,19-diyl)bis-, which is compound 1 used in the synthesis of compound 2 in [Synthesis Example 1]. Compound 1 is manufactured by JNC Corporation under the trade name: XQ1251, and corresponds to the compound in which X is 1,4-phenylene, R is phenyl, and R' is methyl in the above formula (1). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described in detail, but the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to these contents. In addition, the embodiments of the present invention can be appropriately combined. 1. Diamine of the Present Invention The diamine of the present invention is characterized by being a wholly aliphatic diamine having an alkyl or cycloalkyl at the apex of the cage structure.In order to synthesize the diamine of the present invention, it is preferable to use a cage silsesquioxane diamine having an aromatic substituent at the apex of the cage structure as a raw material, because the diamine of the present invention can be easily obtained.As a method for synthesizing the diamine of the present invention, it is preferable to use a nuclear hydrogenation method in the presence of a noble metal catalyst.

[0012] In the diamine of the present invention, preferred specific examples of X in formula (1) include alkylenes such as methylene, ethylene, propylene, pentylene, hexylene, octylene, decylene, and dodecylene, and cycloalkylenes such as cyclobutylene, cyclopentylene, cyclohexylene, and bicyclo[2.2.1]heptane-2,3-diyl (norbornane-2,3-diyl).

[0013] Among these, more preferred as X in formula (1) is propylene or cyclohexylene.

[0014] Preferred specific examples of R in the formula (1) include cyclopentyl and cyclohexyl.

[0015] Among these, more preferred as R in formula (1) is cyclohexyl.

[0016] 2. Polyamic Acid and Polyimide of the Present Invention The diamine of the present invention can be reacted with a tetracarboxylic dianhydride to obtain a polyamic acid having a cage-shaped silsesquioxane structure in the main chain. Furthermore, by dehydrating the obtained polyamic acid, a polyimide having a cage-shaped silsesquioxane structure in the main chain can be synthesized. In this specification, the polyamic acid also includes a form in which a part of the polyamic acid molecule is dehydrated and cyclized in the reaction process to become a partial polyimide. In the synthesis of polyamic acid and polyimide, the tetracarboxylic dianhydride used is not particularly limited. Specific examples thereof include pyromellitic dianhydride (pyromellitic anhydride), 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 2,3,3',4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, Anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 2,2',3,3'-diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 2,2',3,3'-diphenyl sulfone tetracarboxylic dianhydride, 2,3,3',4'-diphenyl sulfone tetracarboxylic dianhydride, 1,2,5,6-naphthalene Phthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, bis(dicarboxyphenyl)methane dianhydride, cyclobutane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, cyclohexane tetracarboxylic dianhydride, dicyclohexane tetracarboxylic dianhydride, dicyclopentane tetracarboxylic dianhydride, bis(dicarboxycyclohexyl)ether dianhydride, bis(dicarboxycyclohexyl)sulfone dianhydride, bis(dicarboxycyclohexyl)methane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride, meta-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, para-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,2,3,4-butane tetracarboxylic dianhydride, ethylene glycol bis(anhydrotrimellitate) (trade name; Rikacid) TMEG-100, manufactured by New Japan Chemical Co., Ltd.), or a tetracarboxylic dianhydride having a cage-shaped silsesquioxane structure represented by formula (2). One or more of these can be used.

[0017] TIFF2025009145000003.tif4189

[0018] In formula (2), R 3 are independently an alkyl having 1 to 45 carbon atoms, an aryl having 6 to 16 carbon atoms, or an arylalkyl having 7 to 16 carbon atoms; in the alkyl having 1 to 45 carbon atoms, at least one hydrogen may be replaced by fluorine; in the aromatic ring in the aryl having 6 to 16 carbon atoms and the arylalkyl having 7 to 16 carbon atoms, at least one hydrogen may be replaced by fluorine or an alkyl having 1 to 6 carbon atoms; in the alkylene in the arylalkyl having 7 to 16 carbon atoms, the number of carbon atoms is 1 to 10, and at least one -CH2- may be replaced by -O-; and R 4 is independently methyl or phenyl.

[0019] Among these, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, cyclobutanetetracarboxylic dianhydride, bis(dicarboxycyclohexyl)methane dianhydride, and 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride are preferred.

[0020] In the synthesis of the polyamic acid of the present invention, a polyesteramic acid can be obtained by using a polyhydric alcohol in addition to the above-mentioned tetracarboxylic dianhydride. In the synthesis of the polyester amic acid, the polyhydric alcohol used is not particularly limited as long as it has two or more hydroxyl groups.

[0021] 3. Polyamide of the Present Invention The diamine of the present invention can be reacted with a dicarboxylic acid or a derivative thereof to give a polyamide having a cage-shaped silsesquioxane structure in the main chain. In the synthesis of polyamide, the dicarboxylic acid used is not particularly limited. Specific examples thereof include aromatic carboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, 2,5-dimethylterephthalic acid, 4,4'-biphenyldicarboxylic acid, 3,3'-biphenyldicarboxylic acid, naphthalenedicarboxylic acid, fluorenedicarboxylic acid, benzophenone-2,4'-dicarboxylic acid, benzophenone-4,4'-dicarboxylic acid, 4,4'-dicarboxyphenylsulfone, and 2,2-bis(4-carboxyphenyl)hexafluoropropane, aliphatic carboxylic acids such as malonic acid, methylmalonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and 1,4-phenylenediacetic acid, and alicyclic carboxylic acids such as 1,4-cyclohexanedicarboxylic acid, cyclopentamethylenedicarboxylic acid, and decalindicarboxylic acid. In addition, compounds in which at least one hydrogen atom of any of the hydrocarbon groups in these compounds is replaced with fluorine or trifluoromethyl, such as tetrafluorophthalic acid, can also be used. Some of these compounds contain isomers, and may be a mixture of these isomers. One or more of these can be used.

[0022] Of these, phthalic acid, isophthalic acid, terephthalic acid, 4,4'-biphenyldicarboxylic acid, naphthalenedicarboxylic acid, fluorenedicarboxylic acid, benzophenone-4,4'-dicarboxylic acid, 4,4'-dicarboxyphenyl sulfone, 2,2-bis(4-carboxyphenyl)hexafluoropropane, glutaric acid, adipic acid, pimelic acid, 1,4-phenylenediacetic acid, 1,4-cyclohexanedicarboxylic acid, cyclopentamethylenedicarboxylic acid, and tetrafluorophthalic acid are preferred.

[0023] In the synthesis of the polyamide of the present invention, the reaction can be carried out under milder conditions by using a derivative of a dicarboxylic acid instead of the above-mentioned dicarboxylic acid. As the derivatives thereof, it is possible to use acid halides such as carboxylic acid chlorides, and active esters such as 1-hydroxybenzotriazolyl esters, 2,4-dinitrophenyl esters, N-hydroxysuccinimide esters, etc. When these derivatives are used, the most preferred are acid halides.

[0024] 4. Polyamide-imide of the present invention The diamine of the present invention can be reacted with a tricarboxylic acid or a derivative thereof to obtain a polyamideimide. Specific examples include trimellitic acid, trimellitic anhydride, trimellitic anhydride chloride, and trimellitic trichloride, with trimellitic anhydride chloride being preferred.

[0025] A solvent is used in the reaction for synthesizing the polymer of the present invention. There are no particular limitations on the solvent as long as it can dissolve the raw material monomers used in the synthesis reaction or the product polymer. Specific examples of the solvent used in the synthesis reaction include toluene, xylene, mesitylene, cyclopentanone, cyclohexanone, N-methyl-2-pyrrolidone, formamide, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylimidazolidinone, dimethylsulfoxide, hexamethylphosphoric triamide, sulfolane, γ-butyrolactone, tetrahydrofuran, dioxane, dichloromethane, chloroform, and 1,2-dichloroethane. Cyclohexanone, N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and tetrahydrofuran are preferred. These solvents may be used alone or in combination.

[0026] The polymer obtained in the present invention may be used as a liquid polymer or a solid polymer after removing the reaction solvent, but from the viewpoint of shortening the time required for film formation, it is preferable to leave the reaction solvent intact and use the polymer as a polymer solution or gel.

[0027] 5. Thin films and free-standing films of the present invention These polymer solutions can be used to manufacture thin films or self-supporting films. The method of coating a substrate to form a thin film is not particularly limited, but includes methods using an applicator, comma motor, doctor blade, dispenser, or squeegee, methods using a rotating device such as a spin coater, and printing methods such as screen printing and inkjet printing. In order to coat uniformly, it is preferable to use a wet coating method. Among the wet coating methods, when producing a small amount, the spin coating method, which is simple and capable of forming a homogeneous film, is preferable. When productivity is important, the microgravure coating method, gravure coating method, dip coating method, die coating method, wire bar coating method, bar coating method, reverse coating method, roll coating method, slit coating method, dipping method, spray coating method, meniscus coating method, kiss coating method, reverse kiss coating method, air knife coating method, curtain coating method, flow coating method, printing method, inkjet method, flexographic printing method, screen printing method, rod coating method, etc. are preferable. The wet coating method can be appropriately selected from these methods depending on the required film thickness, viscosity, curing conditions, etc. In addition, when coating, the solvent composition and concentration of the oligomer solution may be the same as those during polymerization, but the reaction solvent may be partially or entirely removed by vacuum concentration or the like, and then the concentration and solvent composition may be adjusted to the optimum level before coating.

[0028] When producing a free-standing film, a cast molding method is used in which a polymer solution is used to coat a substrate that has been subjected to a release treatment using the above-mentioned method and then peeled off, and when producing a structure, a resin molding method such as press molding, injection molding, or various 3D printer molding methods (ejection lamination methods) can be used with a raw material powder, etc., using a mold as necessary. After molding, the mold can be removed and the mold can be fully cured, or the mold can be fully cured while still in the mold, or in the case of a molding method that does not use a mold, the molded body can be fully cured as is.

[0029] In addition, the method of drying the solvent (pre-baking) after applying these solutions can be the same as the method used for forming normal insulating films, protective films, low dielectric members, optical members, etc. For example, an oven, a hot plate, or an infrared furnace can be used. After applying the solution, it is preferable to evaporate the solvent and dry the film at a relatively low temperature, usually in two stages, 1 to 60 minutes on a hot plate or in an oven at 60 to 100°C and 5 to 90 minutes on a hot plate or in an oven at 120 to 180°C, although it depends on the type and mixing ratio of each component used in preparing the solution. After drying, the main curing (main baking) conditions vary depending on the type and mixing ratio of each component, but it is preferable to heat the film in an oven at a temperature of usually about 180 to 500°C, preferably 180 to 450°C, and more preferably 180 to 400°C. The heating temperature may be constant or may be increased stepwise. The heating time varies depending on the type of polymer, but is usually about 5 to 240 minutes, preferably 10 to 180 minutes, and more preferably about 30 to 90 minutes. The heat treatments for drying (pre-baking) and main curing (main baking) may be carried out in air, in a nitrogen atmosphere, or under reduced pressure.

[0030] In the production of these thin films or self-supporting films, a solvent with low surface tension may be used in combination for the purpose of improving coating properties. Specific examples of solvents with low surface tension include alkyl lactate, 3-methyl-3-methoxybutanol, tetralin, dialkyl malonate (specific example: diethyl malonate), isophorone, ethylene glycol monoalkyl, ethylene glycol phenyl acetate, ethylene glycol monoalkyl ether (specific example: ethylene glycol monobutyl ether), diethylene glycol monoalkyl ether (specific example: diethylene glycol monoethyl ether), triethylene glycol monoalkyl ether, and propylene glycol monoalkyl ether (specific example: propylene glycol monobutyl ether). Many of these solvents have low solubility in the polymer compared to the reaction solvent, so it is preferable to add an amount that does not cause precipitation of the dissolved components.

[0031] Furthermore, it is also possible to add a surfactant used for the purpose of improving coatability, an antistatic agent used for the purpose of preventing static electricity, or a silane coupling agent or a titanium-based coupling agent used for the purpose of improving adhesion to the substrate.

[0032] Preferred silane coupling agents include vinyltrimethoxysilane, vinyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.

[0033] The polyamic acid, polyamide, or polyamideimide polymer of the present invention preferably has a weight average molecular weight (Mw) of 1,000 to 2,000,000, more preferably 5,000 to 500,000, as measured by GPC and calculated as polystyrene. This range is determined in consideration of the film coating properties and film strength. The polyamic acid also includes partially imidized polyamic acid.

[0034] The protective film of the present invention is a film that coats an object to make the surface of the object flatter or to protect the surface or interior of the object from external chemical or physical damage.

[0035] The insulating film of the present invention is a film that has the function of electrically insulating electrically conducting metal wiring from the same in electronic components including a multilayer wiring structure inside an LSI.

[0036] The optical member of the present invention is a material that has the function of confining an optical signal in a specific region and guiding it from the input end to the output end in an optical functional element such as an optical fiber or optical wiring.

[0037] The electrical solid-state device of the present invention refers to a solid-state circuit formed of solid-state elements such as transistors and diodes, and a semiconductor integrated circuit device which is an integration of such circuits. EXAMPLES

[0038] The present invention will be described in more detail below with reference to Synthesis Examples, Examples and Comparative Examples, but the present invention is not limited to these Synthesis Examples and Examples.

[0039] The abbreviations for the measurement items in the synthesis examples are shown below. Mw: Weight average molecular weight Mn: Number average molecular weight

[0040] Next, the measuring apparatus and analysis conditions used in the Synthesis Examples and Examples are shown below. <ft-ir> Equipment: JASCO FT / IR-7000 Measurement conditions: KBr method, room temperature < 1 H-NMR> Equipment: JEOL Ltd. JNM-GSX400 (400MHz) Solvent: deuterated chloroform Measurement temperature: room temperature Internal standard: tetramethylsilane < 29 Si-NMR> Equipment: JEOL Ltd. JNM-GSX400 (79MHz) Solvent: deuterated chloroform Measurement temperature: room temperature Internal standard: tetramethylsilane <gpc> Equipment: Waters 2695 Separation Module / 2414 Differential Refractometer Solvent: Phosphoric acid-DMF mixed solution (phosphoric acid / DMF=0.6 / 100 weight ratio) Flow rate: 0.40mL / min Column temperature: 50℃ Column used: Waters HSPgel RT MB-M Standard sample for calibration curve: TSK standard polystyrene manufactured by Tosoh Corporation <Dielectric property evaluation (relative permittivity and dielectric loss tangent measurement)> Equipment: AET, INC. Cavity resonator TE mode 10 GHz, 28 GHz and Anritsu Corporation Vector network analyzer MS46522B-043 <Heat resistance evaluation (thermal decomposition temperature measurement)> Equipment: Rigaku Corporation TG-DTA8120 / S Atmosphere: Nitrogen Temperature rise conditions: 40℃→800℃, 10℃ / min

[0041] [Synthesis of diamine] [Synthesis Example 1] Di[9,19-methyl(4-aminocyclohexyl)]-1,3,5,7,11,13,15,17-octacyclohexylpentacyclo[11.7.1.1 3,11 .1 5,17 .1 7,15 Synthesis of decasiloxane (compound 2) Compound 2 corresponds to the compound of formula (1) in which X is 1,4-cyclohexylene, R is cyclohexyl, and R' is methyl. TIFF2025009145000004.tif46161 Using a 500mL high pressure reactor equipped with a stirrer, compound 1 (66.80g; 50.0mmol), Ru / C (Ru 5% by weight, containing water) (0.4043g; Ru 0.2mmol) (manufactured by N.E. Chemcat), and cyclopentyl methyl ether (303.94g) were reacted at 80°C for 7 hours under a hydrogen atmosphere of 0.2MPa. The catalyst was then separated into solid and liquid by filtration, and anhydrous magnesium sulfate was added to the filtrate and dehydrated. After that, solid-liquid separation was performed by filtration, and the filtrate was concentrated using a rotary evaporator. The obtained solid concentrate was dried under reduced pressure at 70°C for 6 hours to obtain a white solid (yield: 50.31g, yield: 84%). As a result of GPC measurement of the obtained compound 2, a single peak was confirmed, and the presence of impurities was not confirmed. The IR spectrum of this compound 2 is shown in Figure 1. From the IR spectrum of Figure 1, the aromatic ring-derived peak at 1598 cm , which is seen in the IR spectrum of the raw material compound 1 (Figure 2), was observed by the nuclear hydrogenation reaction. -1 , 1619cm -1 and 3016~3072cm -1 The disappearance of was confirmed. NMR analysis confirmed that the compound had the structure of compound 2. The chemical shifts are shown below. 1 H-NMR(400MHz,CDCl3)δ0.50(m, 6H), 0.70(m, 8H), 1.02(m, 3H), 1.21(m, 43H),1.55(m, 6H),1.71(m, 43H), 1.93(m, 2H), 2.07(m, 1H), 2.60(m, 1H). 29 Si-NMR (79MHz, CDCl3) δ -22.77, -69.80, -71.65. Compound 1 used in the synthesis of compound 2 and represented on the left side of the above synthesis reaction formula is XQ1251 manufactured by JNC Corporation, which corresponds to the compound in which X is 1,4-phenylene, R is phenyl, and R' is methyl in the above formula (1). In the above synthesis reaction formula, Ph is phenyl, Me is methyl, and Cy is cyclohexyl.

[0042] [Synthesis of polyamic acid] [Synthesis Example 2] Synthesis of polyamic acid (PAA1) In a 300mL four-necked separable flask equipped with a thermometer, a stirrer, and a nitrogen inlet tube, compound 2 (21.7962g; 15.6mmol) as a diamine and dehydrated N-methyl-2-pyrrolidone (142.8101g) as a reaction solvent were added, and after the solids were completely dissolved, the mixture was placed under a nitrogen atmosphere at room temperature, and pyromellitic anhydride (3.4056g; 15.6mmol) was further added as a tetracarboxylic dianhydride. After stirring for 16 hours, 168.00g of a uniform, transparent polyamic acid (PAA1) solution with a solid content of 15.0% by weight was obtained. The Mw of the polyamic acid (PAA1) was 107,500, the Mn was 43,800, and the Mw / Mn was 2.5.

[0043] [Polyimide synthesis] [Synthesis Example 3] Synthesis of polyimide (PI1) 15 mL of polyamic acid (PAA1) solution was taken with a micropipette and applied to a cleaned silicon substrate in a square shape of 10 cm x 10 cm or more using an applicator. The solvent was evaporated on a hot plate at 80°C for 30 minutes, and the substrate was heated in an oven at 150°C for 15 minutes. The oven was then heated to 350°C over an hour, and the substrate was further heated at 350°C for 30 minutes for final curing (main baking), resulting in a transparent polyimide (PI1) in the form of a cured film 200 μm thick.

[0044] [Synthesis of polyamic acid] [Comparative Synthesis Example 1] Synthesis of polyamic acid (PAA2) In a 300mL four-necked separable flask equipped with a thermometer, a stirrer, and a nitrogen inlet tube, compound 1 (20.8551g; 15.6mmol) as a diamine and dehydrated N-methyl-2-pyrrolidone (137.4230g) as a reaction solvent were added, and after the solids were completely dissolved, the mixture was placed under a nitrogen atmosphere at room temperature, and pyromellitic anhydride (3.4056g; 15.6mmol) was further added as a tetracarboxylic dianhydride. After stirring for 16 hours, 161.68g of a uniform, transparent polyamic acid (PAA2) solution with a solid content of 15.0% by weight was obtained. The Mw of the polyamic acid (PAA2) was 193,600, the Mn was 79,500, and the Mw / Mn was 2.5.

[0045] [Polyimide synthesis] [Comparative Synthesis Example 2] Synthesis of polyimide (PI2) 15 mL of polyamic acid (PAA2) solution was taken with a micropipette and applied to a cleaned silicon substrate in a square shape of 10 cm x 10 cm or more using an applicator. The solvent was evaporated on a hot plate at 80°C for 30 minutes, and the substrate was heated in an oven at 150°C for 15 minutes. The oven was then heated to 350°C over an hour, and the substrate was further heated at 350°C for 30 minutes for final curing (main baking), resulting in a transparent polyimide (PI2) in the form of a cured film 200 μm thick.

[0046] [Example 1], [Comparative Example 1] The polyimides (PI1) and (PI2) obtained in Synthesis Example 3 and Comparative Synthesis Example 2 were evaluated for dielectric properties (dielectric constant and dielectric tangent) and heat resistance (thermal decomposition temperature) as follows. <Method of measuring dielectric properties (dielectric constant and dielectric tangent)> The polyimide cured film obtained in the above synthesis example was peeled off from the silicon substrate to prepare a measurement sample for dielectric property evaluation. In order to reduce the effect of the moisture content in the measurement sample, the measurement sample was left to stand for one day in an electronic desiccator with a relative humidity of 10% RH in advance. The evaluation of dielectric properties was started after the measurement sample was left to stand for 60 minutes or more in a laboratory with an air conditioner set at a temperature of 20°C. The shift and attenuation of the resonant frequency of the dielectric property evaluation sample were measured using a cavity resonator (TE mode 10 GHz, 28 GHz) manufactured by AET, INC. connected to a vector network analyzer (MS46522B-043 manufactured by Anritsu Corporation), and the dielectric properties of the relative permittivity and dielectric loss tangent (tan δ) were calculated using the company's software. Since the film thickness greatly affects the measurement accuracy, the total thickness of the prepared sample was measured at five points using a digimatic micrometer manufactured by Mitutoyo Corporation, and the average value was used for calculation. The results are shown in Table 1. <Heat resistance evaluation method> The heat resistance was evaluated by measuring the thermal decomposition temperature using the measurement sample for the dielectric property evaluation and using the 5% weight loss temperature as the heat resistance evaluation. The results are shown in Table 1.

[0047] [Table 1] TIFF2025009145000005.tif67170It was found that the cured film of Example 1 had both a low dielectric constant and a low dielectric tangent, and exhibited excellent dielectric properties, compared to the relative dielectric constant and dielectric tangent of the cured film of Comparative Example 1 shown in Table 1. As for heat resistance, the 5% weight loss temperature of the cured film of Example 1 was 37°C lower than that of Comparative Example 1, but was still 500°C or higher, indicating excellent heat resistance.

[0048] [Polyamide synthesis] [Synthesis Example 4] Synthesis of polyamide (PA1) The diamine compound 2 (21.7962 g; 15.6 mmol) synthesized above was dissolved in N-methyl-2-pyrrolidone (141.4741 g) and stirred under ice cooling. To this solution, terephthalic acid dichloride (3.1698 g; 15.6 mmol) was added as a solid. The mixture was returned to room temperature and stirred for 3 hours, and the reaction solution was poured into 100 mL of methanol to precipitate a polymer. The precipitate was collected by filtration, and the white solid was dried under reduced pressure to obtain 21.56 g of polyamide (PA1). The Mw and Mn measured by GPC were 52,100 and 28,400, respectively.

[0049] [Synthesis of polyamide-imide] [Synthesis Example 5] Synthesis of polyamideimide (PAI1) Trimellitic anhydride chloride (3.2877g; 15.6mmol) and triethylamine (16.0mL) were dissolved in N-methyl-2-pyrrolidone (80.0g) and stirred under ice cooling. A solution of the diamine compound 2 (21.7962g; 15.6mmol) synthesized above dissolved in N-methyl-2-pyrrolidone (145.0g) was added dropwise to the solution to carry out a reaction. The precipitated triethylamine hydrochloride was filtered off, and 240.40g of a uniform transparent polymer solution with a solid content of 10.0% by weight was obtained. The result of measuring this solution by GPC was that Mw was 78,300 and Mn was 33,800. 1 mL of the polymer solution was taken with a micropipette and applied to a 10 cm x 10 cm glass substrate using the spinner method, then heated on a hot plate at 100°C for 3 minutes. Next, it was placed in an oven at 150°C in a nitrogen atmosphere and heated for 1 hour, resulting in a pale yellow thin film of polyamideimide (PAI1) with a thickness of approximately 900 nm. [Industrial Applicability]

[0050] The diamine of the present invention is a wholly aliphatic diamine that does not have an aromatic ring structure and has a cage silsesquioxane structure. In addition, the wholly aliphatic diamine of the present invention can be reacted with a tetracarboxylic dianhydride to obtain a polyamic acid, polyimide, polyamide, or polyamideimide polymer having a wholly aliphatic cage silsesquioxane structure, preferably a wholly alicyclic cage silsesquioxane structure, which is essential for low dielectric members and colorless and transparent optical members, introduced into the main chain. Furthermore, the cured film obtained from these polymers can be suitably used as an insulating member or optical member for electronic devices and electronic equipment that handle high frequencies.< / gpc>

Claims

1. A diamine represented by formula (1): In formula (1), X is independently an alkylene having 1 to 12 carbon atoms or a cycloalkylene having 4 to 8 carbon atoms; in the alkylene having 1 to 12 carbon atoms, at least one hydrogen may be replaced by fluorine; R is independently an alkyl having 1 to 45 carbon atoms or a cycloalkyl having 4 to 8 carbon atoms; in the alkyl having 1 to 45 carbon atoms, at least one hydrogen may be replaced by fluorine; and at least one -CH 2 - may be replaced by -O-, in the cycloalkylene having 4 to 8 carbon atoms, at least one hydrogen may be replaced by fluorine or alkyl having 1 to 3 carbon atoms; and R' is independently methyl or cyclohexyl, with the proviso that when X is alkylene having 1 to 12 carbon atoms; in the alkylene having 1 to 12 carbon atoms, at least one hydrogen may be replaced by fluorine, R is alkyl having 1 to 45 carbon atoms; in the alkyl having 1 to 45 carbon atoms, at least one hydrogen may be replaced by fluorine, and at least one -CH 2 - may be replaced by -O-, but not -.

2. 2. The diamine of claim 1, wherein X is propylene or cyclohexylene; and R is methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tertiary butyl, cyclopentyl, or cyclohexyl.

3. 2. The diamine of claim 1, wherein X is 1,4-cyclohexylene; and R is cyclohexyl.

4. A polyamic acid obtained by reacting a raw material containing the diamine according to claim 1 and a tetracarboxylic dianhydride.

5. A polyimide obtained by cyclizing the polyamic acid according to claim 4 .

6. A polyamide obtained by reacting a raw material containing the diamine according to claim 1 and a dicarboxylic acid or a derivative thereof.

7. A polyamideimide obtained by reacting a raw material containing the diamine according to claim 1 and a tricarboxylic acid or a derivative thereof.

8. A thin or self-supporting film comprising the polyamic acid according to claim 4, the polyimide according to claim 5, the polyamide according to claim 6, or the polyamideimide according to claim 7.

9. An insulating film using the film according to claim 8 .

10. A protective film comprising the film according to claim 8.

11. A low dielectric member using the film according to claim 8.

12. An optical member using the film according to claim 8.

13. 10. An electrical solid-state device using the insulating film according to claim 9.

14. An electrical solid-state device using the protective film according to claim 10.

15. The low dielectric member according to claim 11; The ability to generate, convert, transmit, and process radio frequencies and an electronic device having at least one capability selected from the group consisting of: electronic equipment.

16. An optical device using the optical member according to claim 12.

Citation Information

Patent Citations

  • Resin / metal laminate excellent in dielectric property and circuit board

    JP2012107121A

  • Resin composition, polyimide metal laminate using the same, and electronic circuit substrate

    JP2013018806A